Natural Resources of India and Organisation for Their Coordinated Survey, Assessment and Studies - Planning Commission (Planning Commission, 1951)
The wealth of a nation is the skill and energy of its people plus its proved natural resources. Agriculture and industry ultimately depend upon soil, water, minerals and timber. In developing the economy of a country, the first step is to locate, measure and evaluate the natural resources available, and the second step is to plan development on these proved resources. A resource has no value until it is located and measured. In fact a resource does not officially exist till it is discovered, measured and evaluated. Once discovered and evaluated it becomes part of the capital of the nation.
Resources and Scientific Research Division Planning Commission
Resources and Scientific Research Division Planning Commission